Discourses on the performance gap of agriculture in a green economy: a Q-methodology study in Indonesia. Issue 1 (1st January 2017) - Amaruzaman, Sacha; Leimona, Beria; van Noordwijk, Meine; Lusiana, Betha
ABSTRACT: Gaps exist between aspirations of 'green agriculture', which protects biodiversity and ecosystem services, and the reality on the ground. Using Q-methodology, we explored expert opinion in Indonesia on the contributing factors to the gaps. Q-methodology indicated three dominant discourses on 'green agriculture' and groups of experts who prioritize them: (1) endorsers of regulations and innovations; (2) providers of resources for access to capital, technology and knowledge; and (3) proponents of green economy (GE) and land-use planning (LUP). Group 1 pointed out the importance of endorsing incentives to reduce the gap, while Group 2 reckoned that building smallholders' capacity and providing them with access to capital, technology, and knowledge are needed to green agricultural practices. Group 3 described the importance of integrating environmental value into the gross domestic product and earmarking sources derived from environmental levies for greening the agricultural sector. All discourses recognized the importance of scientific policy formulation. Groups 1 and 3 agreed that non-synchronization of LUP between national and local governments highly contributes to the gap. Groups 2 and 3 perceived that ecosystem services from the agricultural sector have not been sufficiently understood to promote green agricultural development. By simultaneously addressing the gaps on each level and understanding how each factor contributes to the gap, we propose a set of recommendations to improve the implementation of green agriculture in Indonesia by creating a platform that all three groups can recognize and support.EDITED BY Dagmar Mithöfer